Desempenho agronômico de híbridos de milho, em função da aplicação foliar de fungicidas - Vilela, Rafael Goncalves [UNESP] (2012)
The objective of the study was to evaluate the agronomic performance of corn hybrids (AG 8088, BG 7049, CD 327, CD 384, CD 351 and CD 321) at function of the foliar application of two fungicides (piraclostrobina + epoxiconazol and azoxistrobina + ciproconazol) at pre-tasseling of the culture. The experiment was conducted In Selviria - MS, in the experimental Farm of the Faculty of Engineering of Ilha Solteira - SP (UNESP), Brazil, during the harvest of 2008/09. The treatments were disposed in randomized complete block design in a factorial scheme 6 x 3 (corn hybrids x fungicides), with four replications. There was valued plant height and of insertion of the ear, number of rows of grains by ear and of grains by row, incidence of foliar diseases, weight of hundred grains and productivity. The results were submitted to the analysis of variance, and the hybrids and fungicides compared by Tukey test (P<0.05). For data analysis were used the software SISVAR. The foliar application of the fungicides piraclostrobina + epoxiconazol and azoxistrobina + ciproconazol in pre-tasseling of the culture the corn reduced the incidence of foliar diseases, nevertheless, was not sufficient to provoke growth of productivity. The hybrids CD 321, AG 8088 and CD 351 were highlighted by the higher yield obtained.